Chinese theology and translation - Wei, Sophie Ling-chia, author.
1 online resource.
Keywords: "This book uncovers the Jesuits mystic theological interpretation in the translation of the Book of Changes (the Yijing) in their mission in China. The book analyses how Jesuit Figurists incorporated their intra-lingual translation of the Yijing, the classical and vernacular use of Chinese language and the imitation of Chinese literati's format, and the divinization of Yijing numbers into their typological exegesis. By presenting the different ways in which Jesuit Figurists' Christianized the Yijing and crafted a Chinese version of Jesus and Christian stories onto the Chinese classics, this book reveals the value of Jesuit missionary-translators. The Chinese manuscripts the Figurists left behind became treasures which have been excavated and displayed in this book. These treasures reveal the other side of the story, the side not much shown in past scholarship on the Figurists. These handwritten manuscripts on the Christianized Yijing are a legacy which continues to impact the European understanding of Chinese history and civilization in later centuries. A first analysis of these manuscripts in Chinese, the book will be of interest to scholars working on the history of Christianity in China and East Asian Religion and Philosophy"--